2022
DOI: 10.3390/ijerph192013323
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Positive Education Intervention for Academic Boredom and Intrinsic Motivation among College Students: A Quasi-Experimental Study

Abstract: (1) Background: The influence of academic boredom and intrinsic motivation on students’ learning and achievements is receiving more attention from scholars. Nevertheless, studies on how intervention decreases academic boredom and promotes intrinsic motivation during study remain unexplored. (2) Purpose: The purpose of this study is to investigate whether positive education intervention based on the PERMA model would help Chinese college students with learning-related academic boredom, class-related academic bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
2
0
2
Order By: Relevance
“…Second, we found support for Hypothesis three (H3), again highlighting associations in the expected directions. These data were in line with evidence on the relationship between motivation/self-regulation processes and wellbeing (Ryan and Deci, 2000 ; Marler et al, 2021 ; Juntunen et al, 2022 ) and, in particular, the well-demonstrated negative role of Amotivation (Vallerand et al, 1997 ; Baker, 2004 ; Ratelle et al, 2007 ; Marler et al, 2021 ) and the role of Intrinsic Motivation dimensions as key resources (Ryan and Deci, 2000 ; Jie et al, 2022 ) for students' psychological health. However, when considering extrinsic motivation, we made no hypothesis on the direction of associations with anxiety/depression due to the mixed evidence reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we found support for Hypothesis three (H3), again highlighting associations in the expected directions. These data were in line with evidence on the relationship between motivation/self-regulation processes and wellbeing (Ryan and Deci, 2000 ; Marler et al, 2021 ; Juntunen et al, 2022 ) and, in particular, the well-demonstrated negative role of Amotivation (Vallerand et al, 1997 ; Baker, 2004 ; Ratelle et al, 2007 ; Marler et al, 2021 ) and the role of Intrinsic Motivation dimensions as key resources (Ryan and Deci, 2000 ; Jie et al, 2022 ) for students' psychological health. However, when considering extrinsic motivation, we made no hypothesis on the direction of associations with anxiety/depression due to the mixed evidence reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite, at the highest level of autonomous functioning, intrinsic motivation describes students who perceive a sense of inherent enjoyment and pleasure from academic life (i.e., understanding new things; surpassing oneself; stimulating sensations). This results in feelings of freedom, satisfaction, and wellbeing (Ryan and Deci, 2000 ; Jie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Young children are often unable to sit still, and it is still unknown how their remarkable restlessness and the tendency to be quickly bored develops. Although some studies have examined the relationship between schoolchildren’s levels of boredom in class and their grades, and how to decrease boredom in class (Jie et al, 2022 ; Tze et al, 2016 ), very few studies have investigated children’s boredom in their daily lives, such as situations in which children are likely to be bored, the behaviors they likely exhibit when bored, and how children learn to cope with boredom as they grow older. In fact, if children can learn to avoid boredom, they will be better able to cope with boredom, engage in enriching activities, and maintain mental health later in life.…”
Section: Children’s Proneness To Be Boredmentioning
confidence: 99%
“…(2021) estudiaron variables motivacionales que influencian metacognitivamente en el rendimiento de las tareas a través del instrumento psicométrico Junior Metacognitive Awareness Inventory, determinando los efectos y significación positiva al considerar a la motivación en el proceso de enseñanza; los estudiantes priorizaron su aprendizaje y ejecutaron la abstención, flexibilidad, memoria de trabajo, mayor esfuerzo para logar el conveniente nivel de conocimiento. investigaciones consideraron al maestro como copartícipe de la motivación estudiantil, propiciando en el aula la necesidad de conocer y aplicar adecuadamente estrategias motivacionales (Rodrígues et al, 2021;Jie et al, 2021; Nieto-Márquez, García-Sinaucia y Pérez, 2021); intervenir con estrategias motivadoras en la enseñanza, suscita la retroalimentación, autocontrol y maleabilidad cognoscitiva; por lo que es necesario solicitar el cambio direccional del maestro y lograr las características mencionadas (Makhambetova et al, 2021), y adaptarlas a las necesidades actuales de tácticas que apoyen el aprendizaje individual, personalizado, considerando las particularidades de género, estilo de aprendizaje, y motivación para aprender.…”
Section: Gráfico I: Motivación Como Principal Preocupación Docente Re...unclassified
“…Como se infiere del anterior párrafo, el rol docente es de suma importancia para propiciar un entorno educativo motivador, ya sea percibido como facilitador o controlador del aprendizaje, pues, como manifiestan Jie et al (2021), el docente motivador y facilitador hace que los estudiantes canalicen mejor sus emociones negativas y a la vez equilibrar su psiquismo. Complementa Quelal (2020), que el uso deficiente por parte de los docentes de estrategias motivadoras, genera clases monótonas y repetitivas, sin estimular el interés por aprender; mientras que hay investigadores que consideran que intervenir y acompañar el aspecto psicológico y social subjetivo de los estudiantes, debe acontecer durante toda su formación profesional (Siqueira et al, 2020;Li et al, 2021).…”
Section: Gráfico I: Motivación Como Principal Preocupación Docente Re...unclassified